Analysis of Failure Characteristics and Strength Criterion of Coal-Rock Combined Body with Different Height Ratios - Tuo Wang; Zhanguo Ma; Peng Gong; Ning Li; Shixing Cheng (Advances in Civil Engineering)
In underground mining and roadway support engineering of coal mine, the coal and rock layers bear loads together; therefore, the deformation and mechanical characteristics of the coal-rock combined bodies are not the same as those of the pure coal or rock bodies. In this paper, conventional triaxial compression tests of coal-rock combined bodies with different height ratios were conducted. And the stress and deformation characteristics of coal-rock combined body were studied and the experimental results were analyzed with different strength criteria. The results show that the peak stress, elastic modulus, and strength reduction coefficient of coal-rock combined body are negatively correlated with the ratio of coal to coal-rock combination height and positively correlated with the confining pressure; the coal-rock combination shows obvious ductility under 10 MPa confining pressure. Under the conventional triaxial condition, the shear failure was the main cause of the lateral deformation of the coal body in the coal-rock combination, which was much larger than that of the rock body. The circle deformation value, volume strain value, and the deformation rate in the postpeak stage of coal-rock combination are much higher than those in the prepeak stage. Mohr–Coulomb and general Hoek–Brown strength criterion fit the experimental results well.